Penerapan Model Project Based Learning Berbantuan Media Papercraft untuk Meningkatkan Keterampilan Berbicara Siswa Kelas II SDN 1 Ngronggah - Gusti Riski Rahmadani; Husna Imro'athush Sholihah; Ika Nurwulandari (Paedagogie, 2026)
Speaking abilities, particularly those of students, are vital to the learning process' success. According to field conditions, some kids' speaking abilities are still subpar. This situation necessitates the deployment of a different or successful innovation to enhance pupils' speaking abilities. The purpose of this study is to describe how the project-based learning model with papercraft medium is used and to ascertain if the project-based learning model with papercraft has improved the speaking abilities of SDN 1 Ngronggah second-grade children. Tono Suwartono's classroom action research (CAR) is the methodology employed. The planning stage, action implementation, observation, and reflection were all part of the two cycles (cycle I and cycle II) of the research process. Sixteen second-graders from SDN 1 Ngronggah served as the study's subjects. Techniques for gathering data included testing, interviews, observation, and documentation. Students' speaking abilities improved when the project-based learning paradigm was implemented with the use of papercraft medium. The findings demonstrated that students' speaking abilities had improved, as seen by their increased speaking fluency, improved intonation, clear expression, and capacity for basic conversations with instructors and classmates. Four students (25%) still required follow-up in the subsequent cycle, whereas twelve students (75%) attained mastery in the first cycle. The percentage of pupils who attained mastery rose to 15 (94%) in the second cycle. Based on the study's findings, it can be said that the papercraft-assisted project-based learning paradigm is useful for teaching Indonesian and may help students become more professional speakers.